2023
DOI: 10.1093/gbe/evad072
|View full text |Cite
|
Sign up to set email alerts
|

A Kiss of Deep Homology: Partial Convergence in the Genomic Basis of Hypertrophied Lips in Cichlid Fish and Human Cleft Lip

Abstract: The genomic loci generating both adaptive and maladaptive variation could be surprisingly predictable in deeply homologous vertebrate structures like lips. Variation in highly conserved vertebrate traits such as jaws and teeth in organisms as evolutionarily disparate as teleost fishes and mammals are known to be structured by the same genes. Likewise, hypertrophied lips that have evolved repeatedly in Neotropical and African cichlid fish lineages could share unexpectedly similar genetic bases themselves and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…Cichlid fishes have acquired a huge diversity in their oral morphologies, reflecting ecological and trophic specializations (Albertson and Kocher, 2006;Kocher, 2004;Lecaudey et al, 2021Lecaudey et al, , 2019. Hypertrophied lips, one of the most prominent examples of oral diversity, have been independently acquired in cichlids inhabiting each of the East African Great Lakes, as well as in the Nicaraguan crater lakes and South American rivers (Henning et al, 2017;Kautt et al, 2020;Masonick et al, 2023Masonick et al, , 2022. Several hypotheses have been proposed for the adaptive roles of hypertrophied lips, such as for effectively sucking prey out from narrow crevices (Lukas et al, 2015), reducing mechanical stress during foraging in rocky habitats (Fryer, 1972;Greenwood, 1974), and facilitating prey detection by providing an enlarged area for taste receptors (Arnegard and Snoeks, 2001;Oliver and Arnegard, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cichlid fishes have acquired a huge diversity in their oral morphologies, reflecting ecological and trophic specializations (Albertson and Kocher, 2006;Kocher, 2004;Lecaudey et al, 2021Lecaudey et al, , 2019. Hypertrophied lips, one of the most prominent examples of oral diversity, have been independently acquired in cichlids inhabiting each of the East African Great Lakes, as well as in the Nicaraguan crater lakes and South American rivers (Henning et al, 2017;Kautt et al, 2020;Masonick et al, 2023Masonick et al, , 2022. Several hypotheses have been proposed for the adaptive roles of hypertrophied lips, such as for effectively sucking prey out from narrow crevices (Lukas et al, 2015), reducing mechanical stress during foraging in rocky habitats (Fryer, 1972;Greenwood, 1974), and facilitating prey detection by providing an enlarged area for taste receptors (Arnegard and Snoeks, 2001;Oliver and Arnegard, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transcriptome comparisons between hypertrophied and normal lips of cichlids in Lake Tanganyika (Colombo et al, 2013) and South American crater lakes (Manousaki et al, 2013) have identified some differentially expressed genes (DEGs) as candidates for lip hypertrophy; however, their primary regulators remain to be elucidated. In addition, quantitative trait locus (QTL) mapping (Henning et al, 2017) and genome-wide association study (GWAS) (Masonick et al, 2023) have been conducted to elucidate the genomic loci responsible for hypertrophied lips in the cichlids of Lake Victoria and Lake Malawi. These genome-wide studies concluded that lip hypertrophy was a polygenic trait involving several candidate genes.…”
Section: Introductionmentioning
confidence: 99%